A responsabilidade criminal em acidentes de viação com vitimas mortais - Rebisco, Paulo Jorge Dinis (2018)
Road accidents, particularly those will result victims, of their various types, are facts that directly contribute to the deviation of what is normal life of the people. Accidents with fatalities play a preponderant role in society, and its effects are devastating. However, it is important to assess whether the course from the occurrence of the events (accident) to the judicial decision (sentence) is structured in such a way that what citizens expect from the judicial system is materialized, that is, justice is done. It is also important to understand whether the investigation of the accident is capable of materializing the seriousness of the phenomenon, so that the judicial decision-maker can not rely on the arguments for the correct application of the law to the specific case. The study will focus in particular on road accidents involving mortal victims, in which criminal responsibility has been attributed, to at least one of the interveners that took place between 01 January 2009 and 31 December 2015, in the district of Setúbal. The final judgments will be analyzed, with respect to the penalties applied, by correspondence or not, with the facts proven.